Goal vs. gold? Unveiling the business performance of Malaysian family takaful operators - Muhammad Zuki, Mohd Faizuddin; Ishak, uhammad Arif Fadilah; Roja, Muhammad Izzuddin Halim (Universiti Teknologi MARA Selangor, 2025)
This paper aims to assess the business performance of family takaful operators in Malaysia. The study examines the impacts of the operator’s specifics and economic predictors on the relationship with the operator’s performance captured by Return on Asset (ROA). The operator’s specifics include fee and commission income, zakat payments, underwriting risk, liquidity, and firm size, while the economic predictors include Gross Domestic Products (GDP) and inflation rate. Using four regression estimations, which are the Ordinary Least Squares (OLS) model, the Robust OLS model, the Cluster Robust OLS model and the Feasible Generalised Least Squares (GLS) model, this study employed a balanced panel data approach to nine Malaysian family takaful operators for ten years, 2013-2022. The findings for the four estimation models affirmed that fee and commission income, underwriting risk, and liquidity significantly impact the ROA but not firm size and GDP. The findings also exhibit a significant relationship between zakat payment and the inflation rate on ROA in the different estimation models. Several works of literature are very interested in Malaysian takaful business performance without specifying the scope of family takaful business. Thus, this study aims to unveil the performance of family takaful businesses on Malaysian family takaful operators. This paper brought its novelty by conceptualising the fee and commission income and zakat payment as new proxies for measuring performance. The study’s implications admonish the family takaful operators’ recommendation to increase the operators’ performance.